Paul Ibou : Metamorphosis (Illegible Color Variation Book) - Michiels, Ivo (Antwerpen : Monas, 1968)
Innovative artists' book by the great Belgian designer Paul Ibou (pseudonym for Vermeersch) with die-cut pages and plastic cutouts.
Nederlands
boek
Keywords: Ibou, Paul